Key to the soldiers of Angularitermes Emerson with a new species from Brazilian Amazonia (Isoptera: Termitidae: Nasutitermitinae) - Carrijo, Tiago F.; Rocha, Mauricio M.; Cuezzo, Carolina; Cancello, Eliana M. (Zootaxa, 2011)
An identification key based on characters of the soldier caste is provided for species of Angularitermes. Soldiers of previously described species in the genus, A. clypeatus, A. nasutissimus, A. orestes, A. pinocchio and A. tiguassu, are illustrated along with a new species, Angularitermes coninasus, n. sp., that is described and illustrated from soldier and worker castes. Samples of the new species were collected from epigeal nests at the Brazilian Amazon rainforest. The soldier of A. coninasus, n. sp. is distinguished from its congeners by having a short conical frontal tube, much wider at its base.